A case of phagophobia: when fear consumes us - Loureiro, Estela Rita (2016)
Introduction: Phagophobia or choking phobia is a psychiatric disorder characterized by the fear of suffocating or choking when swallowing food or tablets. It may lead to a refusal to eat. Little is known about the prevalence of this disease, but the diagnosis is often delayed and this may increase the risk of complications. Organic pathology and other eating disorders must be excluded. The therapy is multidisciplinary and the general practitioner has an important role in management. Case presentation: We report the case of a 10 year-old girl who was seen by her family doctor due to the sudden onset of dysphagia with solid food over a two-week period. She lost 22% of her body weight over the next two months. Physical examination and laboratory tests were normal. A pediatric consultant using a bio-psycho-social approach found ‘a fear of choking while eating’. She was referred to the child-psychiatry service of the local children's hospital with suspected anorexia nervosa and functional or organic dysphagia. With worsening of her clinical status with selective and restrictive feeding, including severe weight loss (26% of her previous body weight), she was hospitalized and later transferred to Magalhães Lemos psychiatric hospital. The diagnosis of phagophobia (choking phobia) was made and she was treated with antidepressant, anxiolytic, and antipsychotic medications. She also received cognitive behavioral therapy and clinical improvement was observed. Currently, she is receiving ongoing psychiatric treatment to help her to deal with her fear and to regain the weight she lost. Commentary: Early identification and referral of patients with this problem are essential. Knowledge of the differential diagnosis and available therapy are important. A trusting relationship between the family doctor and teenage patients is helpful for early detection of important signs. Coordination with secondary care services is necessary for close monitoring of these patients